An ultra-high H2S-resistant gold-based imidazolium ionic liquid catalyst for acetylene hydrochlorination. (30th July 2019) - Yue, Yuxue; Wang, Bolin; Sheng, Gangfeng; Lai, Huixia; Wang, Saisai; Chen, Zhi; Hu, Zhong-Ting; Zhao, Jia; Li, Xiaonian
Abstract : Enhancement of the sulfur resistance of gold-based catalysts is significantly relevant and highly desirable for the development and large-scale applications of these catalysts. Abstract : Enhancement of the sulfur resistance of gold-based catalysts is significantly relevant and highly desirable for the development and large-scale applications of these catalysts. In this study, a supported gold-based imidazolium ionic liquid catalyst was shown to be ultra-high resistant towards sulfur poisoning during the acetylene hydrochlorination reaction. To explore the impact of H2 S on the as-prepared catalysts, accelerated laboratory-scale poisoning tests were performed, and characterization was achieved by various instruments. The adsorption of H2 S on the active sites of Au/AC catalysts, occupying gold species, prevented the reactants, including C2 H2 and HCl, from being adsorbed on the catalyst surface. With respect to the Au–IL/AC catalysts, the unique Au–IL colloid complexes, formed from ionic liquids, impart resistance towards H2 S; moreover, the ionic liquid layer on the activated carbon surface can prevent the deposition of sulfur impurities on catalysts; in addition, the adsorption of H2 S on the ionic liquid layer is a dynamic equilibrium process, and the adsorption equilibrium constant at 180 °C (453 K) is 0.24 L mg −1 . The interaction between H2 S and the ions in the ionic liquid is weaker than the binding force within ions in the ionic liquid itself.